Mad Women: Living with a Label of Borderline Personality Disorder - Buckley, Emily Jessica (2013)
Throughout history, society has sought to label people who have exhibited behaviour perceived as abnormal. Since the enlightenment, psychiatry has endeavoured to provide explanations for such abnormal behaviours by labelling people with mental health diagnoses. Historically, women have been prime candidates for labelling, accused of witchcraft and subjected to punishment in the Middle Ages, labelled with hysteria and confined in asylums by the Victorians, and more contemporarily, assigned with the borderline personality disorder diagnosis. This critical review seeks to explore the borderline personality disorder diagnosis and examine the implications it has for women who are given this label. Literature suggests that there are many problems with the borderline personality disorder diagnosis, since it is poorly defined and its current system of classification is considered to be failing. This diagnosis is based upon gender-appropriate traits and behaviours and the judgement of these to be abnormal in women who are diagnosed with borderline personality disorder. The criteria for the diagnosis are such that it is considered to be gender-biased and as a result women are more vulnerable to being labelled with borderline personality disorder than men. Borderline personality disorder consists of traits and characteristics which can be destructive and have a severe impact upon the lives of individuals, such as extreme emotional reactions, intense anger, self-harm and unstable relationships. These traits also tend to be associated with negativity and therefore stigmatising attitudes around the diagnosis are prevalent, particularly within mental health services and amongst professionals working within them. Women diagnosed with borderline personality disorder tend to be labelled as untreatable, manipulative, blameworthy, attention-seekers and undeserving of care. This inevitably leads to poor relationships between these women and mental health professionals and can have a damaging impact on their experiences with psychiatric services and the quality of care they receive.